Boosting the abscopal effect using immunogenic biomaterials with varying radiation therapy field sizes: biology contribution - Yasmin-Karim, Sayeda; Ziberi, Bashkim; Wirtz, Johanna; Bih, Noella; Moreau, Michele; Guthier, Romy; Ainsworth, Victoria; Hesser, Jürgen; Makrigiorgos, G. Mike; Chuong, Michael D.; Wei, Xiao; Nguyen, Paul L.; et al. (International journal of radiation oncology, biology, physics, 2022)
Purpose - Persistent immunosuppression in the tumor microenvironment is a major limitation to boosting the abscopal effect, whereby radiation therapy at 1 site can lead to regression of tumors at distant sites. Here, we investigate the use of radiation and immunogenic biomaterials (IBM) targeting only the gross tumor volume/subvolume for boosting the abscopal effect in immunologically cold tumors. - Methods and Materials - To evaluate the abscopal effect, 2 syngeneic contralateral tumors were implanted in each mouse, where only 1 tumor was treated. IBM was administered to the treated tumor with 1 fraction of radiation and results were compared, including as a function of different radiation therapy field sizes. The IBM was designed similar to fiducial markers using immunogenic polymer components loaded with anti-CD40 agonist. Tumor volumes of both treated and untreated tumors were measured over time, along with survival and corresponding immune cell responses. - Results - Results showed that radiation with IBM administered to the gross tumor subvolume can effectively boost abscopal responses in both pancreatic and prostate cancers, significantly increasing survival (P < .0001 and P < .001, respectively). Results also showed equal or superior abscopal responses when using field sizes smaller than the gross tumor volume compared with irradiating the whole tumor volume. These results were buttressed by observation of higher infiltration of cytotoxic CD8+ T-lymphocytes in the treated tumors (P < .0001) and untreated tumors (P < .0001) for prostate cancer. Significantly higher infiltration was also observed in treated tumors (P < .0001) and untreated tumors P < .01) for pancreatic cancer. Moreover, the immune responses were accompanied by a positive shift of proinflammatory cytokines in both prostate and pancreatic tumors. - Conclusions - The approach targeting gross tumor subvolumes with radiation and IBM offers opportunity for boosting the abscopal effect while significantly minimizing healthy tissue toxicity. This approach proffers a radioimmunotherapy dose-painting strategy that can be developed for overcoming current barriers of immunosuppression especially for immunologically cold tumors.
Online verfügbar: 13. September 2021, Artikelversion: 6. Januar 2022
Gesehen am 28.05.2024